Influence of Alkali Treatment on the Surface Area of Aluminium Dross - Zauzi, N.S.A.; Zakaria, M.Z.H.; Baini, R.; Rahman, M.R.; Mohamed Sutan, N.; Hamdan, S. (Hindawi Publishing Corporation, 2016)
Aluminium dross is an industrial waste from aluminium refining industry and classified as toxic substances. However, the disposal of dross as a waste is a burden to aluminium manufacturer industries due to its negative effects to the ecosystem, surface, and ground water. Therefore the purpose of this study is to evaluate the influence of sodium hydroxide (NaOH) on the surface area and pore size of aluminium dross. There were 3 stages in the treatment activities, which were leaching, precipitation, and calcination process. The optimum result from this study was the surface area of aluminium dross increases from 10.1 m2/g up to 80.0 m2/g at 40°C, 1% NaOH, and 15-minute reaction time. Thus, aluminium dross has a potential to be converted into other useful material such as catalyst and absorbent. The benefit of this research is that the hazardous industrial waste can be turned into wealth to be used in other applications such as in catalytic activities and absorber in waste water treatment. Further investigation on the physicochemical of aluminium dross with different acid or alkali should be conducted to get deeper understanding on the aluminium dross as a catalyst-type material.